Encouragement of the Personnel of the State Labor Service of Ukraine to Implement International Experience within Labor Protection Management - O. A. Lukianykhina; V. O. Lukianykhin; I. V. Kolesnyk; K. О. Khamlyka (Law and Safety)
The subject matter of the research of the motives of state officials are socio-economic and legal relations that arise in the process of improving the activities of the State Labor Service of Ukraine (SLS) in the field of “Labor Protection”. The object of the research is the system of state management of labor protection and technology of personnel incentives in the regional departments of the SLS. The purpose of the work is theoretical substantiation and development of recommendations for improving the activities and increasing motivation of the staff of the SLS of Ukraine in Sumy region, in particular the implementation of the experience of advanced world countries into the management strategies. Implementation of the current regulatory base in the field of labor protection in Ukraine, in accordance with international requirements, requires high qualification and motivation of the staff of the relevant executive authorities, the development of effective tools to stimulate the efficient work of those state officials.